Reliability of Two Recently Developed Procedures Assessing Biological Maturity by Ultrasound Imaging—A Pilot Study - Nicole Hutmacher; Jasmin D. Busch; Eva Rüeger; Michael Romann; Patric Eichelberger (Children, 2024)
During puberty, the biological maturity of children of the same chronological age differs. To generate equal opportunities for talent selection in youth sports, the athlete’s biological maturity should be considered. This is often assessed with a left hand and wrist radiography. Alternatively, ultrasound (US) could be advantageous, especially by avoiding ionizing radiation. This pilot study aimed to assess intrarater and interrater reliability of an experienced and a non-experienced examiner in an US-based examination of the knee in 20 healthy females (10–17 years). Epiphyseal closure at five anatomical landmarks was staged (stages 1–3) and its interrater and intrarater reliabilities were analyzed using Cohen’s kappa (k). Interrater reliability of the calculation of the ossification ratio (OssR) was analyzed using the Bland-Altman method and intraclass correlation coefficients (ICCs). Interrater reliability for the stages was almost perfect for four landmarks. Interrater reliability ranged from k = 0.69 to k = 0.90. Intrarater reliability for the stages was almost perfect for four landmarks. Intrarater reliability ranged from k = 0.70 to k = 1.0. For the OssR, ICC was 0.930 and a minimal detectable change of 0.030 was determined. To conclude, experienced and non-experienced examiners can reliably assign individuals to different ossification stages and calculate an OssR using US-based imaging of the knee.